Ідентифікувальні суфікси у волинсько-поліських варіантах імен - Нестерчук, Оксана Григорівна; Nesterchuk, Oksana H. (Czech Language Institute of the Czech Academy of Sciences, 2017)
Окрім розглянутих специфічних волинсько-поліських суфікксів, що вжиті в говірках декількох населених пунктів і творять варіанти від різних імен, виявлені також форманти, за допомогою яких варіант імені ідентифікує особу лише в одному населеному пункті.

The suffixes in variations of personal names used to identify the person in one local community and “tied” to a particular carrier were analyzed in the article. The author also found many variations of created with the help of formants that were connected to the full and truncated word creating basis and individual examples of common names the same formants were added too.
Identificational suffixes in variations of personal names of Volyn-Polissia
Keywords: власні назви; варіанти; деривативні суфікси; форманти; апелятиви; proper names; variations; derivation suffixes; formants; appellatives